O uso de marcadores microsatélites no estudo de acasalamento em Melipona scutellaris - Soares, Katiere (2001)
Bees are an integral part of the world's biodiversity. They are responsible for 40 to 90% of the pollination of the native Brazilian tropical flora, according to the ecosystem of which they are part (KERR et al., 1996). There are about 20,000 different species of bees on the planet, varying in size, shape and life habits (VELTHUIS, 1997j _. \ Among all, stingless bees together with melifers reach the highest degree of social evolution (KERR, 1972; VELTHUIS, 1997). Among social bees, meliponines or stingless bees form an important group, rich in species and behavioral variations (VELTHUIS, 1997), in addition to being a very isolated and specialized run group. Their isolation and specialization seems to be largely due to peculiarities of their behavior (KERR et al., 1996). Recently, these bees are spread from Rio Grande do Sul to Central Mexico, in addition to Africa, India, Malaysia and Australia (KERR et al., 1996). Meliponines differ from apines, stinging bees, in that they are more specialized and dependent on climatic and floristic characteristics of their regions of origin, in addition to being less defensive and easy to handle (KERR et al., 1996). They also have particular characteristics that distinguish them from other bees, such as stinging atrophy, reduction and fragility of alar venation and absence of hair in the eyes, with the exception of Trichotrigona extranea (MOURE, 1961).